Analysis of Leading Sectors in Central Tapanuli Regency Using Shift Share and Location Quotient Methods - Situmorang, Elsa Aurel; Sitorus, Melody; br Kaban, Novita Sari (Outline Publisher, 2025)
In the current era of regional autonomy, regional development will become more difficult. Central Tapanuli Regency, as one of the regions located in North Sumatra Province, has various economic sectors that support regional growth. The diversity of economic sectors in this Regency plays an important role in encouraging regional economic growth and community welfare. However, determining the leading sectors is often a challenge for regional governments in formulating economic development policies. In recent years, the Shift Share and Location Quotient methods have been widely used in various studies to analyse regional economic performance. In the Dynamic Location Quotient (DLQ) analysis, the Mining and Quarrying sector, as well as several service sectors such as Government Administration, show good prospects.